THE SOCIAL AND ECONOMIC IMPORTANCE OF CERTIFICATION AND RATIONALIZATION OF EMPLOYMENT SERVICE ENTERPRISES OF AGRO-INDUSTRIAL COMPLEX - L. Kovalev; I. Kovalev (Russian Journal of Agricultural and Socio-Economic Sciences, 2012)
The article considers the economic feasibility of the work on certification and rationalization of employment offices and technical service organizations, agribusiness in the case of the Republic of Belarus. Organizational effectiveness factors of the enterprise is about one-third of the total effect of the activities generated from the implementation of the "internal" reserves of plant efficiency, a significant share of this belongs to the employment factors that are associated with the improvement of the organization of labor groups and direct each worker individually.